Opportunities and obstacles of implementing the idea of Unified Central Asia and Kazakhstan’s position (International relations and international law Journal, 2016)
Article is devoted to considering the features of the convergence process of Central Asia countries and Kazakhstan’s main proposals. Realizing that the world is undergoing changes at the global level, countries of the region recognize the need for integration. Еmerging new threats and challenges may be answered only by combining efforts. This also applies to the Central Asian region. However, it is not so easy to find a common language for five States, having their own goals and interests. The perspective of convergence in the region is mainly viewed through the prism of relations between Kazakhstan, considered the leader of integration initiatives and Uzbekistan, which is distinguished by confident political «voice». The intersection of interests of competing two countries is one of the main factors. Including the question of formation of economic and political space, the problems of cultural space and human capital development are also paid attention.
Keywords: Central Asia; integration; Kazakhstan